2004
DOI: 10.1016/j.jacc.2003.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Association between aldosterone synthase (CYP11B2) polymorphism and left ventricular mass in human essential hypertension

Abstract: Our data suggest that -344C/T polymorphism affects LV mass and thickness in essential hypertension, independent of adrenal aldosterone. A role for intracardiac aldosterone synthesis is hypothesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 26 publications
5
53
0
2
Order By: Relevance
“…However, the association between polymorphisms in the CYP11B2 gene and hypertension is controversial. [7][8][9][10][11][12][13][14][15][16][17][18][19] In the present study, we performed extensive association studies between polymorphisms in CYP11B2 regions and renin-aldosterone profiles and blood pressure values. Our findings in study population II indicate that subjects with the TT genotype of the T(Ϫ344)C polymorphism appear to have higher aldosterone levels in response to PRA levels than those with the TC or CC genotype when renin activity is Ͻ2.45 (e 0.9 ϭ2.45; Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the association between polymorphisms in the CYP11B2 gene and hypertension is controversial. [7][8][9][10][11][12][13][14][15][16][17][18][19] In the present study, we performed extensive association studies between polymorphisms in CYP11B2 regions and renin-aldosterone profiles and blood pressure values. Our findings in study population II indicate that subjects with the TT genotype of the T(Ϫ344)C polymorphism appear to have higher aldosterone levels in response to PRA levels than those with the TC or CC genotype when renin activity is Ͻ2.45 (e 0.9 ϭ2.45; Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The T(Ϫ344)C polymorphism, which is located at the putative binding site for the steroidogenic transcriptional factor, has been reported to be associated with hypertension [7][8][9][10][11][12] and/or hypertension-related phenotypes, such as the plasma aldosterone level, 12,13 urinary aldosterone excretion, 8,14 aldosterone:renin ratio, 7,11,12,[15][16][17] and left ventricular hypertrophy. 18 We reported previously that the T(Ϫ344)C polymorphism was unlikely to influence the blood pressure status in the Japanese population based on an analysis of 4049 subjects recruited from the Suita Study.…”
mentioning
confidence: 99%
“…In the n > 200 EH subgroup (Isaji, 28 Stella 27 ), CC had larger LVESD than TT (p heterogeneity = 0.15, p value < 0.0001, 95% CI −1.02 (−1.45, −0.60)). Under the C/T allelic model, the C allele had larger LVESD values than the T allele in the EH subset 8,27 (I 2 = 0, p heterogeneity = 0.39, p value < 0.0001, 95% CI −0.72 (−0.97, −0.47)).…”
Section: Lvesdmentioning
confidence: 99%
“…When removing the major case of heterogeneity (Olcay 30 ) from the EH group, the results showed that CC had larger LVEDD values than TT (p heterogeneity = 0.96, I 2 = 0%, 95% CI -0.86 (−1.14, −0.59), p value < 0.0001). Under the C/T allelic model, the C allele had larger LVEDD than the T allele in the EH subset 8,27 (I 2 = 0, p heterogeneity = 0.7, p value < 0.0001, 95% CI −0.54 (−0.79, −0.30)).…”
Section: Lveddmentioning
confidence: 99%
“…16 High serum aldosterone can result in hypertrophy of myocardial cells. [17][18][19] In humans, aldosterone synthase is encoded by the CYP11B2 gene. The C-344T variant in the regulatory region of the CYP11B2 gene was associated with enhanced aldosterone production.…”
Section: Discussionmentioning
confidence: 99%